Ggtree: A serialized data object for visualization of a phylogenetic tree and annotation data. Issue 4 (28th September 2022) - Xu, Shuangbin; Li, Lin; Luo, Xiao; Chen, Meijun; Tang, Wenli; Zhan, Li; Dai, Zehan; Lam, Tommy T.; Guan, Yi; Yu, Guangchuang
Abstract: While phylogenetic trees and associated data have been getting easier to generate, it has been difficult to reuse, combine, and synthesize the information they provided, because published trees are often only available as image files and associated data are often stored in incompatible formats. To increase the reproducibility and reusability of phylogenetic data, the ggtree object was designed for storing phylogenetic tree and associated data, as well as visualization directives. The ggtree object itself is a graphic object and can be rendered as a static image. More importantly, the input tree and associated data that are used in visualization can be extracted from the graphic object, making it an ideal data structure for publishing tree (image, tree, and data in one single object) and thus enhancing data reuse and analytical reproducibility, as well as facilitating integrative and comparative studies. The ggtree package is freely available at https://www.bioconductor.org/packages/ggtree . Abstract : The ggtree object is designed to store phylogenetic tree and associated data, and the object itself is a graphic object that can be rendered as an image file. This work will increase the reproducibility and reusability of phylogenetic data, as well as facilitate integrative and comparative studies. Highlights: The phylogenetic tree and diverse accompanying data can be stored in a ggtree graph object, which improves the reproducibility and reusability of phylogenetic data. The phylogenetic tree and associated data can be extracted from the ggtree object, which can be reanalyzed and help various scientific disciplines synthesize their comparative studies and phylogenetic information. The ggtree graph object can be rendered as a static image, and the visualization directives that were previously saved in the object can be reused to display a different tree object in a manner akin to Microsoft Word Format Painter.